Учасник і літописець Української революції: Павло Христюк (до 130-річчя з дня народження) - Шаповал, Ю.; Рижева, Н. (Український історичний журнал, 2020)
Мета статті полягає у створенні життєпису П.Христюка – кооператора, громадсько-політичного діяча, публіциста, автора фундаментальної праці з історії Української революції.
Методологічну основу становить принцип історизму в єдності всіх його компонентів. Дослідження ґрунтується на критичному аналізі архівних і друкованих джерел. Використано мікроісторичний підхід. Наукова новизна полягає у спробі створити на основі раніше недоступних
архівних ресурсів, а також з урахуванням наявних публікацій детальний опис життєвого шляху,
діяльності та значення інтелектуальної спадщини П.Христюка. Використано документи ДПУ–НКВС, що дозволяють пролити світло на обставини його трагічної долі. Усе це дало змогу підготувати найповніший на цей час біографічний нарис, уточнити чимало важливих моментів,
спростувати певні неточності у принагідних публікаціях. Висновки. П.Христюк постає виразним адептом соціалістичних ідей, репрезентантом того прошарку діячів, які накреслювали для України та для всієї Східної Європи поміркований кооперативний соціалізм із демократичною
політичною формою. Водночас він сповідував толерантність до тих, хто мали інші позиції, але
видавалися йому можливими союзниками у виборюванні та збереженні незалежної України.
П.Христюк став не лише учасником, а й літописцем пережитих подій. Його фундаментальна
праця у часи існування СРСР замовчувалася невипадково, адже її автор разом з іншими представниками тодішнього революційного покоління наполягав на тому, що Українська революція суттєво відрізнялася від «петроградської моделі» 1917 р., котра закінчилася більшовицькою
партійною диктатурою. Це, а також політична активність у період Української Центральної Ради
й Директорії УНР, після повернення П.Христюка з вимушеної еміґрації в 1923 р. поставило його
на наступні вісім років у коло тимчасових «попутників» більшовиків, до яких нова влада не мала
довіри. Усе це визначило його долю, коли комуністичний режим розпочав наступ на українську
інтеліґенцію, сфабрикувавши в 1930 р. «справу Спілки визволення України» й готуючи на наступний рік «справу Українського національного центру». Саме за останньою П.Христюк був засуджений і згодом загинув. The purpose of the article is to create a biography of P.Khrystiuk, a cooperator,
a politician, a publicist, an author of the fundamental work about history of the Ukrainian Revolution.
The methodological basis is the principle of historicism in the unity of all its components.
The research is based on a critical analysis of archival and printed sources. The microhistorical
approach was also used. The scientific novelty consists in the attempt to create a detailed description
of the life path, activities and the significance of the intellectual heritage of P.Khrystiuk, based on the
archival resources that were never used before along with those materials that were already published.
The documents of the GPU–NKVD were also used in order to trace the circumstances of P.Khrystiuk’s
tragic fate. All this made it possible to create the most complete biographical sketch so far, to clarify
many important points, to refute certain inaccuracies in those publications in which P.Khrystiuk was
mentioned. Conclusion. P.Khrystiuk appears as a clear adept of socialistic ideas, as a representative
of that group of people who had drawn a moderate, cooperative version of socialism with democratic
political form for Ukraine and for entire Eastern Europe. At the same time, he professed tolerance
towards those activists who used to held different positions, but seemed to him as possible allies in
the building and preservation of independent Ukraine. P.Khrystiuk became not just a participant, but
also a chronicler of events he was involved in. He created a fundamental work on the history of the
Ukrainian Revolution. This work was suppressed during the existence of the USSR not for nothing.
After all, P.Khrystiuk, along with other representatives of the Ukrainian revolutionary generation of
those times, insisted that Ukrainian Revolution differed from the “Petrograd Model” of 1917, which
ended up with Bolshevik’s party dictatorship. The Bolshevik ideologists interpreted such separation of
the specifics of Ukrainian revolution as an assertion of independence of Ukraine. This understanding
of Ukrainian revolution, as well as his previous political activity in times of Ukrainian Central Rada
and the UPR Directory, put P.Khrystiuk (after his return from the forced emigration in 1923) in the
circle of temporary “companions” of Bolsheviks for the next eight years. That is, he was included in
the circle those, to whom the new political authorities had no trust. This determined his fate when
the Bolshevik regime launched an attack on the Ukrainian intelligentsia, fabricating the “Case of the
Union of Liberation of Ukraine” in 1930 and preparing the “Case of the Ukrainian National Center” for
the upcoming year. It was exactly that case, within which P.Khrystiuk was convicted and killed later on.